Use of recycled concrete aggregate - Upadhyay, Urvi Paras; lalwani, Vijay Kishanchand (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Urbanization has generated a high demand for construction aggregates and increased quantities of construction debris that may provide an additional source for aggregates. Recycling of concrete is a relatively simple process. It involves breaking, removing, and crushing existing concrete into a material with a specified size and quality. The quality of concrete with RCA is very dependent on the quality of the recycled material used. Reinforcing steel and other embedded items, if any, must be removed, and care must be taken to prevent contamination by other materials that can be troublesome, such as asphalt, soil and clay balls, chlorides, glass, gypsum board, sealants, paper, plaster, wood, and roofing materials. This investigation includes a descriptive analysis of the supply sources, technology, costs, incentives, deterrents, and market relationships associated with the production of aggregate